LAW, SCIENCE, AND POLITICS - Sellers, Mortimer N. S. (Revista de Direito Brasileira, 2024)
Law, science, and politics belong together because they are three attributes of the same reality. Science begins in the accurate knowledge of reality. Since both law and politics seek (or ought to seek) justice, the science of law and the science of politics must always recur to the science of justice itself. This study of justice begins with the substantive question which form of society will best achieve worthwhile and fulfilling lives for all. The science of law concerns the permissions, prohibitions, and obligations that will best establish justice in any given society or State. The science of politics concerns the epistemic techniques through which we can best discover and establish justice and the law. Justice is the substance. Law is the rules. Politics is the procedures for establishing a just State and society for all.